2018
DOI: 10.1021/acs.chemmater.7b04739
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Electronic Structure upon Li Deintercalation from LiCoPO4 Derivatives

Abstract: On the path toward the design of Li-ion batteries with increased energy densities, efforts are focused on the development of positive electrodes that can maximize the voltage of the full cell. However, the development of novel materials that operate at high voltage, while also showing high efficiency and meeting strict safety standards, is an ongoing challenge. LiCoPO4 is being explored as a possible candidate, as the Co2+/3+ redox couple operates at 4.8 V versus Li+/Li0. The presence of phosphate groups is ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 30 publications
11
38
0
Order By: Relevance
“…Impressively, no O pre‐edge peak features are observed in LCPO–LCO until the depth of 5 nm, which is regarded as the thickness of LCPO (Figure 5j), agreeing well with the STEM measurement. [ 28a,30 ] Nonetheless, at the depth level of 5 nm, the O pre‐edge peak appears, but a weak one compared to that at 10 nm depth, indicating that the hybridization effect between O 2− and Co 3+ is weakened. This change can be understood because the distribution of the electron cloud of O is polarized to P, forming a strong P–O covalent bond.…”
Section: Resultsmentioning
confidence: 98%
“…Impressively, no O pre‐edge peak features are observed in LCPO–LCO until the depth of 5 nm, which is regarded as the thickness of LCPO (Figure 5j), agreeing well with the STEM measurement. [ 28a,30 ] Nonetheless, at the depth level of 5 nm, the O pre‐edge peak appears, but a weak one compared to that at 10 nm depth, indicating that the hybridization effect between O 2− and Co 3+ is weakened. This change can be understood because the distribution of the electron cloud of O is polarized to P, forming a strong P–O covalent bond.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, an interesting relative intensity drop of D has been observed for all the olivine phosphates from the surface to bulk (as the I D / I P 2 shown in Table ). As shown in Figure S1, the O–K pre-edge has been proved sensitive to the Li ion (de)­intercalation, , as the higher oxidation state of the TM ions in the delithiated phase leads to an increase in the number of unoccupied 3d states, which are available for mixing with O 2p states. Therefore, the relatively higher pre-edge intensity in EY modes provides another evidence of surface Li depletion, which is in good agreement with the XPS results.…”
Section: Resultsmentioning
confidence: 99%
“…3d) 23 which is in agreement with previous reports. 22,33,[38][39][40]68 On the other hand, the increase of the Fe/(Fe+Co) ratio in LiCo0.6Fe0.4PO4 is reflected in the two detectable signatures of the Fe 3+ /Fe 2+ and Co 3+ /Co 2+ redox couples, occurring at about 3.5 23 and 4.8 4 V vs.…”
Section: Resultsmentioning
confidence: 99%
“…8,[27][28][29] Moreover, the introduction within Co-based phospho-olivines of the Fe 3+ /Fe 2+ and Mn 3+ /Mn 2+ redox centers reacting at about 3.5 and 4.1 V vs. Li + /Li (LiCo1−xMxPO4 with M = Fe, Mn) has been explored as a viable approach to improve the performances in terms of Li + exchange ability and capacity retention. [30][31][32][33][34][35][36] Promising results have shown that the incorporation of Fe 2+ and Fe 3+ may affect the concentration of punctual defects in the lattice, such as lithium vacancies and anti-site mixing between the 4a and 4c octahedral sites, 37,38 widen the Li + transport channels, 39 and stabilize the Co 3+ /Co 2+ couple, 40 while the presence of Mn 2+ may decrease the particle size and stabilize the electrode surface. 31 Despite of the several papers reported so far on LiCo1−xMxPO4 materials (M = Fe, Mn), [30][31][32][33][34][35]41 most of the work has been focusing on the investigation of the effects of one transition metal, i.e., either manganese or iron.…”
Section: Introductionmentioning
confidence: 99%